As reformas previdenciárias brasileiras sob a pressão neoliberal - Ugino, Camila Kimie (2011)
The aim of this study is to analyze the Brazilian pension reform implemented since the 1990s. The current characteristics of the Social Security system were built in the 1988 Federal Constitution and gradually modified in the reforms. Soon after the promulgation of the Charter, several proposals for Social Pension reform were discussed on the grounds of financial crisis and exhaustion of the system. This debate focuses on the guidelines of a neoliberal state that has gained greater acceptance from the government of Fernando Collor de Melo. Reforms of the Fernando Henrique Cardoso and Luis Inácio Lula da Silva are analyzed mainly with regard to access to pensions, the roofs of retirement, the age limits. Among the consequences this study analyzes the significant changes in Social Security and limited expansion of pension funds. Moreover, given the backdrop of globalized finance, it is concluded that these reforms jeopardized the achievements of social protection built in the 1988 Constitution